Interannual and Long-Term Precipitation Variability Along the Subtropical Mountains and Adjacent Chaco (22–29° S) in Argentina - Ferrero, María Eugenia; Villalba, Ricardo (Frontiers in Earth Science, 2019)
Recent studies documenting climate variability in South America have provided valuable information for understanding current and past dynamics of the climate system. Long meteorological records represent an essential tool to properly characterize climate fluctuations from decadal to multi–decadal scales. Unfortunately, the scarcity of continuous and homogeneous instrumental records is a major constraint to determine long–term variations in South America. Our knowledge of the forcings modulating the hydrological variability in mountains is still limited, despite their importance as freshwater sources for people living in the adjacent piedmonts and lowlands. The objective of this work is to determine the spatial–temporal variability of precipitation in the humid subtropical Andes and the Chaco region in North Western Argentina (NWA). Thirty– four rainfall records covering the common period 1934–1990, partially updated to 2016, were used to extend and identify the dominant patterns of seasonal to annual hydroclimatic variability based on principal components analysis. Intensity and frequency of droughts and pluvials (<5th and >95th percentiles, respectively) were determined for the dominant patterns of variability. Our results show a positive trend in precipitation since 1970s in all temporal patterns and sub–regions. In addition, precipitation variability (both positive and negative extremes) increases during these last decades. Correlation analysis with sea–surface temperatures and wind anomalies during summer, reveal Amazon moisture sources and large–scale oceanic controls on NWA precipitation. The extended precipitation series shows that the frequency of pluvials has increased since the 1970s interrupted by few extreme droughts. This record can be considered representative of precipitation variations across NWA, including different environments in the Chaco, sub–Andes and Puna.